Rates of myocardial infarction and stroke in patients initiating treatment with SGLT2‐inhibitors versus other glucose‐lowering agents in real‐world clinical practice: Results from the CVD‐REAL study. Issue 8 (17th April 2018) - Kosiborod, Mikhail; Birkeland, Kåre I.; Cavender, Matthew A.; Fu, Alex Z.; Wilding, John P.; Khunti, Kamlesh; Holl, Reinhard W.; Norhammar, Anna; Jørgensen, Marit E.; Wittbrodt, Eric T.; Thuresson, Marcus; Bodegård, Johan; et al.
Abstract : The multinational, observational CVD‐REAL study recently showed that initiation of sodium‐glucose co‐transporter‐2 inhibitors (SGLT‐2i) was associated with significantly lower rates of death and heart failure vs other glucose‐lowering drugs (oGLDs). This sub‐analysis of the CVD‐REAL study sought to determine the association between initiation of SGLT‐2i vs oGLDs and rates of myocardial infarction (MI) and stroke. Medical records, claims and national registers from the USA, Sweden, Norway and Denmark were used to identify patients with T2D who newly initiated treatment with SGLT‐2i (canagliflozin, dapagliflozin or empagliflozin) or oGLDs. A non‐parsimonious propensity score was developed within each country to predict initiation of SGLT‐2i, and patients were matched 1:1 in the treatment groups. Pooled hazard ratios (HRs) and 95% CIs were generated using Cox regression models. Overall, 205 160 patients were included. In the intent‐to‐treat analysis, over 188 551 and 188 678 person‐years of follow‐up (MI and stroke, respectively), there were 1077 MI and 968 stroke events. Initiation of SGLT‐2i vs oGLD was associated with a modestly lower risk of MI and stroke (MI: HR, 0.85; 95%CI, 0.72‐1.00; P  = .05; Stroke: HR, 0.83; 95% CI, 0.71‐0.97; P  = .02). These findings complement the results of the cardiovascular outcomes trials, and offer additional reassurance with regard to the cardiovascular effects of SGLT‐2i, specifically as it relates to ischaemic events.